Lack of GPR40/FFAR1 does not induce diabetes even under insulin resistance condition. Issue 6 (6th February 2013) - Matsuda‐Nagasumi, K.; Takami‐Esaki, R.; Iwachidow, K.; Yasuhara, Y.; Tanaka, H.; Ogi, K.; Nakata, M.; Yano, T.; Hinuma, S.; Taketomi, S.; Odaka, H.; Kaisho, Y.
<x xml:space="preserve">Abstract</x> Aims G protein‐coupled receptor/free fatty acid receptor 1 (GPR40/FFAR1) regulates free fatty acid‐induced insulin secretion. This study has been performed to clarify whether or not loss of GPR40/FFAR1 function exacerbates diabetes, that is, whether GPR40 has an essential physiological role in the development of diabetes or not. Methods We generated GPR40/FFAR1 knockout (KO) mice and analysed their phenotypes in vitro and in vivo under the condition of dietary or genetically induced insulin resistance. Results GPR40/FFAR1 KO mice kept on a high‐fat diet became obese, developed glucose intolerance to a similar degree as GPR40/FFAR1 wild‐type (WT) mice. In addition, the phenotype of KO mice harbouring diabetogenic KK background genes showed glucose intolerance at a level similar to level for control KK mice. In both mouse models with insulin resistance, insulin secretion after oral glucose load and homeostasis model assessment‐insulin resistance (HOMA‐IR) did not change between GPR40/FFAR1 KO and WT mice. Although glucose‐induced insulin secretion under high palmitate concentration was significantly lower in KO than in WT islets, pancreatic insulin content and insulin secretion stimulated with glucose alone were not different between KO and WT mice. Conclusions GPR40/FFAR1 has a major role in regulating fatty‐acid‐mediated insulin secretion, but the lack of GPR40/FFAR1 does not exacerbate glucose intolerance and insulin resistance induced by high‐fat diet or diabetogenic KK gene. Our findings indicate that loss of GPR40/FFAR1 function does not play an important role in inducing or exacerbating diabetes.